2017
DOI: 10.1152/ajplung.00379.2016
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar nonselective channels are ASIC1a/α-ENaC channels and contribute to AFC

Abstract: A thin fluid layer in alveoli is normal and results from a balance of fluid entry and fluid uptake by transepithelial salt and water reabsorption. Conventional wisdom suggests the reabsorption is via epithelial Na channels (ENaC), but if all Na reabsorption were via ENaC, then amiloride, an ENaC inhibitor, should block alveolar fluid clearance (AFC). However, amiloride blocks only half of AFC. The reason for failure to block is clear from single-channel measurements from alveolar epithelial cells: ENaC channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 85 publications
(87 reference statements)
5
32
1
1
Order By: Relevance
“…However, the studies of Johnson et al (47) and Lazrak et al (55) showed that rodent ATI and ATII cells express similar channel densities of highly selective Na ϩ channels, with a unitary conductance of~4 pS, most likely composed of the ␣-, ␤-, ␥-ENaC subunits, and nonselective ENaC cation channels, with a conductance of 16 -21 pS, composed of ␣-subunits only (42). It has also been reported that the nonselective channels consist of a combination of the ␣-ENaC subunit and one or more acid-sensing ion channel 1 (ASIC1a) proteins (103). Human alveolar cells also express ENaC (23) and actively transport Na ϩ , albeit at rates lower than in rodent lungs (89).…”
Section: Ion Transport Across Lung Epithelial Cellsmentioning
confidence: 99%
“…However, the studies of Johnson et al (47) and Lazrak et al (55) showed that rodent ATI and ATII cells express similar channel densities of highly selective Na ϩ channels, with a unitary conductance of~4 pS, most likely composed of the ␣-, ␤-, ␥-ENaC subunits, and nonselective ENaC cation channels, with a conductance of 16 -21 pS, composed of ␣-subunits only (42). It has also been reported that the nonselective channels consist of a combination of the ␣-ENaC subunit and one or more acid-sensing ion channel 1 (ASIC1a) proteins (103). Human alveolar cells also express ENaC (23) and actively transport Na ϩ , albeit at rates lower than in rodent lungs (89).…”
Section: Ion Transport Across Lung Epithelial Cellsmentioning
confidence: 99%
“…This raises the possibility that ENaC and their related ASIC proteins (Mano and Driscoll, 1999) may complex to from noncanonical cation channels. This possibility is strongly supported by a study providing evidence for the function of a non-selective cation channels formed by ENaC and ASIC subunits (Trac et al, 2017). These observations indicate that in tissues where only one or two ENaC subunits were identified, these may not only be able for form functional non-canonical ENaC channels but also associate with ASIC subunits and form ENaC/ASIC complexes.…”
Section: Physiological Relevance Of Modulatory Role Of the β Or γ Enamentioning
confidence: 71%
“…In addition, the excess alveolar fluid clearance is an active metabolic process concerning vectorial transport of Na + with water out of alveolar air space, following the osmotic gradient (19). Na + transport from the apical surface to alveolar epithelial cells is associated with amiloride-sensitive Na + channels (ENaC) and in part, by other, less well-characterized cationic channels (20,21). Thus, the mechanism underlying alveolar fluid clearance mediated by Na + transport is becoming clearer.…”
Section: Discussionmentioning
confidence: 99%